Massively multiplayer online games and social capital: A systematic literature review - Gilles R. Scheifer; Robin Samuel (Social Sciences and Humanities Open)
Video gaming has historically been regarded as a pastime with addictive potential and has subsequently been the subject of public scrutiny, in media and academia. In the early 2000s, massively multiplayer online games (MMO) in particular were the locus of addiction-centred debates. However, over time different avenues of research into the outcomes of MMOs have opened up, honing in on social and psychological consequences. The present systematic literature review organises and examines research on the social impact of playing MMOs on their players, analysing a sample of 22 studies leaning on the PRISMA framework. The results indicate that a number of facets adhering to MMO gameplay, such as collective play, game involvement and being part of a community are beneficial to an individual's social capital and related concepts, while gaming time was a significant negative predictor. Offline social capital and leadership research were scarcely present in the collected studies, however the results imply a positive relation between MMO gameplay and these variables. Overall, the results suggest a high potential for transferability of social capital, even so there seems to be diminishing returns. Beyond a certain threshold of gaming time, the relation becomes negative, indicating the importance of balanced engagement.